STUDI KEANEKARAGAMAN JENIS KELELAWAR (CHIROPTERA) PADA BEBERAPA TIPE EKOSISTEM DI CAMP LEAKEY KAWASAN TAMAN NASIONAL TANJUNG PUTING (TNTP), KALIMANTAN TENGAH: Bat's species diversity study (Chiroptera) at some type of ecosystem in Camp Leakey, Taman Nasional Tanjung Puting (TNTP), Central Kalimantan - Saputra, Yudi; Sukandar, Paskal; Suryanda, Ade (Bioma, 2016)
Bat (Chiroptera) is one of mammals that can fly and has population decreased, this caused by habitat loss, trade, and excessive arrested. This research purposed to know about species diversity of bats in Indonesia, especially in Camp Leakey, Taman Nasional Tanjung Puting (TNTP), Central Kalimantan. This research conducted on area study of Camp Leakey, TNTP, Central Kalimantan, at September untill November 2015. Method of this research are descriptive method with misneting technique. Result of this research indicated that studi area of Camp Leakey, TNTP, Central Kalimantan have a high species diversity. Homogenity index were quite high or moderate and inversely proportional to dominant index score were quite low.